Adaptability and use of virtual academic media as predictors of satisfaction with studies in a sample of Peruvian university students - Torres-Miranda, Julio Samuel (2025)
Introduction: The Covid-19 pandemic has brought serious challenges in higher education and more in the process of adaptability. Objective: to determine whether adaptability to university life and the use of virtual academic media predict satisfaction with studies in Peruvian university students. Methods: a non-experimental, cross-sectional, predictive design, 632 university students of both sexes (50.9% women) participated, using the scale of adaptability to university life, the brief scale of satisfaction with studies and the scale of use of virtual academic media. Results: A multiple regression analysis was performed, finding that the independent variables explain 37.8% of the total variance of the criterion variable. Discussion: It can be seen that the level of adjustment to virtual education and the level of use of virtual academic media predict satisfaction with the educational experience at the higher level.